2015
DOI: 10.5114/pwki.2015.52281
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of myocardial strain in patients after transcatheter aortic valve implantation

Abstract: IntroductionEchocardiographic evaluation of regional myocardial function helps to assess the efficacy of therapeutic interventions and to predict the prognosis and clinical outcomes.AimTo assess whether myocardial strain can be useful in estimation of left ventricle (LV) function in patients who have undergone transcatheter aortic valve implantation (TAVI).Material and methodsTwenty-six patients with severe aortic stenosis, who successfully underwent TAVI, were enrolled in the study. Left ventricular peak syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…Achieved procedural increase in AVA was 0.23 cm 2 , decrease in mean and peak gradient was 17.5 mm Hg and 28.6 mm Hg, that is consistent with other reports from BAV studies . These effects has not reached baseline parameters in 1, 6, 12 months follow‐up which emphasizes BAV effectiveness, however AVA had tendency to decrease and transaortic gradients were gradually increasing to the end of observation period.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Achieved procedural increase in AVA was 0.23 cm 2 , decrease in mean and peak gradient was 17.5 mm Hg and 28.6 mm Hg, that is consistent with other reports from BAV studies . These effects has not reached baseline parameters in 1, 6, 12 months follow‐up which emphasizes BAV effectiveness, however AVA had tendency to decrease and transaortic gradients were gradually increasing to the end of observation period.…”
Section: Discussionsupporting
confidence: 89%
“…This highlights the recurrence of AS severity and symptoms with passing time from BAV. Significant increase in LVEF was also confirmed in short‐term and long‐term follow‐up after TAVI, especially in patients with severe impairment of left ventricle at baseline . In spite of these favorable results long‐term mortality remained high, especially in patients scheduled for the palliative treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Meta-analyses of multiple studies in the high-risk populations showed that moderate or severe PVL is an important determinant of mortality regardless of the implanted AVA -aortic valve area; CABG -coronary artery bypass graft; COPD -chronic obstructive pulmonary disease; eGFR -estimated glomerular filtration rate; IQR -interquartile range; LVEF -left ventricular ejection fraction; MI -myocardial infarction; NYHA -New York Heart Association; PCI -percutaneous coronary intervention; STS -The Society of Thoracic Surgeons; TG -transvalvular gradient valve type [24,25]. The occurrence of PVL after TAVI might be more frequent after direct valve implantation without balloon PD, resulting in more frequent PD afterwards [12]. We confirmed that balloon PD can effectively and safely reduce the degree of PVL after TAVI when the primary result of the implantation of the prosthesis is not optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the presence of PVL may worsen clinical outcomes of patients undergoing TAVI [5]. It is present in up to 70% of all patients undergoing TAVI, and more than mild PVL has been reported in about 10-15% of all TAVI patients [1,[6][7][8][9][10][11][12][13][14]. Angio graphy and echocardiography are useful tools to quantify the degree of PVL immediately after deployment of the prosthesis and can be used to identify patients who might benefit from optimisation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 26 TAVR patients, Bochenek et al found that in contrast to the TF approach, TA patients showed no significant improvement in peak systolic longitudinal strain at a 1-y follow-up. 23 Yet, Ando et al reported no significant differences in the immediate post-TAVR GLS between TF and TA groups using transesophageal echocardiograms. 24 In the present study, we found that TA-TAVR and TF-TAVR patients had similar increases in GLS, readmissions risk, and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 97%